Neuron-intrinsic immunity to viruses in mice and humans. (October 2021) - Zhang, Shen-Ying; Harschnitz, Oliver; Studer, Lorenz; Casanova, Jean-Laurent
Abstract : Viral encephalitis is a major neglected medical problem. Host defense mechanisms against viral infection of the central nervous system (CNS) have long remained unclear. The few previous studies of CNS-specific immunity to viruses in mice in vivo and humans in vitro have focused on the contributions of circulating leukocytes, resident microglial cells and astrocytes, with neurons long considered passive victims of viral infection requiring protection from extrinsic antiviral mechanisms. The last decade has witnessed the gradual emergence of the notion that neurons also combat viruses through cell-intrinsic mechanisms. Forward genetic approaches in humans have shown that monogenic inborn errors of TLR3, IFN-α/β, or snoRNA31 immunity confer susceptibility to herpes simplex virus 1 (HSV-1) infection of the forebrain, whereas inborn errors of DBR1 underlie brainstem infections due to various viruses, including HSV-1. The study of human pluripotent stem cell (hPSC)-derived CNS-resident cells has unraveled known (i.e. TLR3-dependent IFN-α/β immunity) and new (i.e. snoRNA31-dependent or DBR1-dependent immunity) cell-intrinsic antiviral mechanisms operating in neurons. Reverse genetic approaches in mice have confirmed that some known antiviral mechanisms also operate in mouse neurons (e.g. TLR3 and IFN-α/β immunity). The search for human inborn errors of immunity (IEIs) underlying various forms of viral encephalitis, coupled with mouse models in vivo, and hPSC-based culture models of CNS and peripheral nervous system cells and organoids in vitro, should shed further light on the cell-specific and tissue-specific mechanisms of host defense against viruses in the human brain.